Mollusc assemblages associated with invasive and native Sargassum species. (1st June 2018) - Veiga, Puri; Torres, Ana Catarina; Besteiro, Celia; Rubal, Marcos
Abstract: Molluscs associated with the native macroalga Sargassum flavifolium and the invasive S. muticum were compared. The influence of habitat complexity provided by each macroalga was considered using biomass and fractal measures as proxies of habitat size and architecture, respectively. Results showed that biomass and fractal area of the alga and abundance, specific richness and diversity of the mollusc assemblages were significantly lower in the invasive macroalga and that mollusc assemblage differed significantly between macroalgae. Among species responsible for dissimilarity between macroalgae, microphytobenthos-grazing gastropods were more abundant in the native seaweed whereas two filter-feeding bivalves were more abundant in the invasive. Results also revealed significant correlations between biomass and fractal area with mollusc assemblages. However, the largest correlation coefficients for fractal area suggest more relevance of habitat architecture. Despite being two closely taxonomically macroalgae, of similar morphology, our findings suggest that the function of invasive macroalga as habitat provider differs from the native and induces changes in its associated fauna, which could imply food web modifications. Graphical abstract: Highlights: Mollusc assemblages associated with native and invasive Sargassum . Invasive Sargassum showed lower biomass and fractal area than the native one. Invasive Sargassum showed lower abundance and diversity than the native one. Invasive Sargassum harboured distinct mollusc assemblages to native species. Correlations of biomass and fractal area with mollusc assemblages were significant.